Navigating digital network: mindfulness as a shield against cyberbullying in the knowledge economy era - Kang, Hongzhe; Wang, Yao; Wang, Min; Al Imran Yasin, Megat; Osman, Mohd Nizam; Ang, Lay Hoon (Springer, 2023)
In the rapidly evolving digital society, people’s daily lives have become intricately woven with online activities, driven by an ever-increasing demand for digital interconnectedness. The internet has bestowed upon them the gift of instantaneous communication with their loved ones, while simultaneously opening doors to global connections. This transformative power of the internet has also spawned a disconcerting issue—cyberbullying. Within the vast expanse of the online world, they witness the proliferation of various forms of harassment and abuse. This not only psychologically but also physically harms on a distressing number of individuals. This study thoroughly explores this disconcerting phenomenon, drawing upon established theories such as the spiral of silence theory and social cognitive theory to unveil the underlying causes of cyberbullying. It embarks on a detailed study into mindfulness, recognizing it as a potential tool to regulate the pernicious effects of cyberbullying. However, a significant knowledge gap persists concerning the cultivation of mindfulness and the intricate factors influencing its effectiveness within the context of cyberbullying. The paper conducts a questionnaire survey encompassing 529 participants to bridge this chasm of understanding. This survey not only provides valuable insights into the repercussions of cyberbullying on internet users but also unveils the potential moderating role of mindfulness in this complex dynamic. The findings unearthed through this study carry profound implications, serving as a clarion call for heightened societal awareness and informed governmental interventions to combat the scourge of cyberbullying.